2021
DOI: 10.1021/acscatal.1c02146
|View full text |Cite
|
Sign up to set email alerts
|

General Chemoselective Suzuki–Miyaura Coupling of Polyhalogenated Aryl Triflates Enabled by an Alkyl-Heteroaryl-Based Phosphine Ligand

Abstract: This study describes a general chemoselective Suzuki–Miyaura coupling of polyhalogenated aryl triflates with the reactivity order of C–Cl > C–OTf using a Pd/L33 catalyst. The methine hydrogen and the steric hindrance offered by the alkyl bottom ring of L33 were found to be key factors in reactivity and chemoselectivity. With the Pd/L33 catalyst, a wide range of polyhalogenated (hetero)­aryl triflates, which were independent of the substrates and of the relative positioning of the competing reaction sites, coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
(25 reference statements)
0
26
0
Order By: Relevance
“…, –Cl > –OTf) is an incredibly attractive strategy and would significantly broaden the choice of synthetic routes in actual applications. 7 However, only a few reports demonstrating Suzuki coupling and a single example of the Stille reaction have demonstrated the possibility of inverting the conventional reactivity order in cross-coupling reactions, which is still highly difficult to achieve ( Scheme 1B ). 7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, –Cl > –OTf) is an incredibly attractive strategy and would significantly broaden the choice of synthetic routes in actual applications. 7 However, only a few reports demonstrating Suzuki coupling and a single example of the Stille reaction have demonstrated the possibility of inverting the conventional reactivity order in cross-coupling reactions, which is still highly difficult to achieve ( Scheme 1B ). 7 …”
Section: Introductionmentioning
confidence: 99%
“… 7 However, only a few reports demonstrating Suzuki coupling and a single example of the Stille reaction have demonstrated the possibility of inverting the conventional reactivity order in cross-coupling reactions, which is still highly difficult to achieve ( Scheme 1B ). 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Fu's, [10b] Neufeldt's, [10f] and our research group [10g] have reported this inversion of the common reactivity order of C−Cl>C−OTf in the Suzuki‐Miyaura reaction, with one example in the Stille coupling reaction [11] . In our recent study, we designed and synthesized a novel type of heteroaryl‐based phosphine ligand, in which the preagostic interaction and the steric hindrance offered by the C2‐alkyl group enabled palladium‐catalyzed chemoselectivity in C−Cl for the Suzuki‐Miyaura reaction involving polyhalogenated aryl triflates with aryl boronic acids [10g] . Herein, we report our efforts in the first palladium‐catalyzed chemoselective C−Cl (over C−OTf) borylation reaction (Scheme 1C).…”
Section: Methodsmentioning
confidence: 87%
“…14 a – d In our design, we chose indole as the skeleton because the electronic-biased heterocyclic core and its bicyclic structure may have a different electronic and steric influence on the reaction. 15 In addition, this ligand offers the following advantages in modular synthetic processes: (1) versatile ligand precursors can be prepared from readily available indoles as well as indole carboxylic acids; (2) the substituents of the N atom and the aromatic ring provide additional electronic tunability; (3) the acidic hydrogen at the C2-position provides a facial installation of the amide group through direct deprotonation; and (4) the installation of phosphine motifs to the electron-donating C3-position could increase the electron density of the phosphine motifs and facilitate the oxidative process (Scheme 2). Starting with commercially available N -substituted indoles or indole-2-carboxylic acids, a series of phosphine ligands with an indole-amide-based backbone was prepared and tested in palladium-catalyzed cross-coupling reactions (Scheme 2).…”
mentioning
confidence: 99%